2018
DOI: 10.1186/s12861-018-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal ontogeny of Astatotilapia burtoni – a direct-developing model system for the evolution and development of the teleost body plan

Abstract: BackgroundThe experimental approach to the evolution and development of the vertebrate skeleton has to a large extent relied on “direct-developing” amniote model organisms, such as the mouse and the chicken. These organisms can however only be partially informative where it concerns secondarily lost features or anatomical novelties not present in their lineages. The widely used anamniotes Xenopus and zebrafish are “indirect-developing” organisms that proceed through an extended time as free-living larvae, befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(112 citation statements)
references
References 113 publications
9
102
0
Order By: Relevance
“…In contrast to the zebrafish where adult color pattern develops indirectly during a post-embryonic metamorphic phase (Parichy et al, 2009), the vertical bars in H. latifasciatus develop directly and are already visible at a time when the larvae are still feeding from their yolk. This is in line with previous reports on the direct development of other morphological traits of African cichlid fishes (Woltering et al, 2018).…”
Section: Melanic Pattern Development: H Latifasciatus Vs Other Telesupporting
confidence: 93%
“…In contrast to the zebrafish where adult color pattern develops indirectly during a post-embryonic metamorphic phase (Parichy et al, 2009), the vertical bars in H. latifasciatus develop directly and are already visible at a time when the larvae are still feeding from their yolk. This is in line with previous reports on the direct development of other morphological traits of African cichlid fishes (Woltering et al, 2018).…”
Section: Melanic Pattern Development: H Latifasciatus Vs Other Telesupporting
confidence: 93%
“…This would be in agreement with the findings of Lleras-Forero et al, which showed potential interaction between the notochord and somites, reinforcing the pattern of the forming vertebral components. Work in ‘indirect’ developing salamanders and ‘direct’ developing fish give support to this proposition ( Figure 1B ; Slijepčević et al, 2018 ; Woltering et al, 2018 ). By this model, the early formation of the mineralized, segmented notochord in zebrafish may dissociate, or even expose, these two patterning mechanisms.…”
mentioning
confidence: 70%
“…(4) Direct development strategies (e.g. Woltering et al, 2018 ), which have a contemporary activation of pattern mechanisms; here a somite signal masks a putative influence of the notochord. (5) In tetrapod vertebrates, in which the influence of the notochord is reduced or masked, the vertebrae arise from somites, and cartilage-derived tissue forms an arcocentrum (light blue).…”
mentioning
confidence: 99%
“…For example, Parichy et al used the flexion angle as developmental criteria, but, as in goldfish, this criterion seems not obvious to apply for clownfish, as in our conditions it is difficult to measure in late‐stage larvae due to their pigmentation, which covers the notochord. To determine flexion of the notochord, we used the position of the hypural bones, as it is commonly used in descriptions of larval fish development . As in many fish species, hypural bones are the first skeletal structures to appear in the caudal fin .…”
Section: Discussionmentioning
confidence: 99%